(untitled) (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2025)
This study analyzes the impact of implementing the Statement of Financial Accounting Standards (PSAK) 409 on the effectiveness of zakat management at the National Amil Zakat Agency (BAZNAS) of Majalengka. PSAK 409 is a specific accounting standard for zakat management aimed at enhancing transparency, accountability, and accuracy in the financial reporting of zakat institutions. The research employs a quantitative approach using financial report data from periods before and after the implementation of PSAK 409, along with surveys conducted among employees and staff involved in zakat management, which were then analyzed statistically. The results indicate a significant improvement in the transparency of financial reporting, operational efficiency, and public trust toward BAZNAS Majalengka. The implementation of PSAK 409 has also contributed to more optimal collection and distribution of zakat funds. These findings provide important implications for zakat institutions in adopting professional and reliable financial standards, thereby supporting a modern and sustainable zakat governance system.